A qualidade de vida de homens trabalhadores rurais inseridos no contexto da soja - Oliveira, Jeane Cristina Anschau Xavier de (2020)
to analyze the effects of life, health and work conditions on the quality of life of male rural workers inserted in the soybean cultivation. Method: this is a methodological and empirical study. The methodological study refers to the process of elaborating and validating the face and content of a research instrument called “Life and health conditions of rural workers”; as for the empirical study, this is a quantitative and epidemiological approach, with a cross-sectional cutout, including a sample of 299 male rural workers inserted in the soybean cultivation, aged between 18 and 64 years old, working in farms and warehouses for producing and storing soybeans in the town of Sinop-MT. The research instruments were: 1. Questionnaire “Life and health conditions of rural workers”, which was built and, subsequently, had its face and content validated by a committee of experts in the areas of worker’s health and men’s health; 2. International Physical Activity Questionnaire (IPAQ), used to assess the level of physical activity; 3. CAGE Questionnaire: acronym for its four questions (Cut down, Annoyed by criticism, Guilty and Eye-opener), in order to assess alcohol addiction. 4. Work Context Assessment Scale (EACT, as per its Portuguese acronym). 5. Human Labor Cost Scale (ECHT, as per its Portuguese acronym), in order to assess work conditions; 6. Whoqol-bref, in order to measure the self-assessment of quality of life and the scores of the physical, psychological, social relations and environment domains in the studied sample. The life, health and work conditions were considered as independent variables (explanatory) and the self-assessment of quality of life and its domains were considered as dependent variables (outcome). Descriptive analyzes were performed based on the measurement of relative and absolute frequencies and measures of central tendency and dispersion (mean, median, standard deviation, variance and breadth). The inferential analysis involved a Shapiro-Wilk normality test that found that the sample consists of non-parametric data. In order to perform the bivariate analysis, Mann- Whitney hypothetical tests were used (for variables with two categories); Kruskal-Wallis (for variables with more than two categories) the latter followed by Dunn's Post Hoc test; and association test (Chi- square). In order to analyze the correlation between numerical variables, Spearman’s nonparametric test was used. In order to assess the reliability of the scales, Cronbach’s Alpha test was applied. In order to identify the scales in the work context that have the most impact on quality of life, factor analysis was applied. In order to analyze the joint influence of the explanatory variables, multivariate analysis was performed using the regression method via Generalized Additive Model for Location, Scale and Shape (GAMLSS). All analyzes considered p<0.05 as significant. Results: regarding the face and content validation, the questionnaire was validated with a general CVI of 0.99 and with a CVI above 0.90 for all domains, thus demonstrating the validity and relevance of the elaborated instrument. The self- assessment of quality of life obtained a score of 75.6 points; physical domain, 80.54 points; psychological, 75.66 points; social relationships, 75.89 points; and environment, 66.90 points. The sample consisted of men with a mean age of 34 years; browns (45.8%); singles (35%); with elementary education (41%); Catholics (60%); with a mean of 1.41 children; born in Maranhão (29%); who are “live- in” employees (58%); who use their own transport (66%); with a formal contract (98%); non-union members (66%); developing the role of agricultural machinery operators (29%); with a mean monthly income of 2,141.92 Brazilian reais and a real income of 3,195.46 Brazilian reais in the harvest; with a mean workload of 45 hours per week outside the harvest and 73 hours per week during the harvest; with a mean of 10 years of rural work and 7 years of work with soy. Most of the workers were overweight (42%); with moderate to high cardiovascular risk (64.6%); 42.1% with blood pressure outside normal standards; 17% were smokers; 14% were alcohol addicts; 8.4% use medication daily; 29.8% were sedentary; 30% manipulated pesticides; 16.4% suffered an accident at work at some point in their lives; 55.5% said they were exposed to sunlight at work; 53.5% do not use sunscreen; 68.6% reported exposure to noise; 43.1% mentioned exposure to vibration; 62.9% said they were exposed to dust; 97% described the use of PPE; 73.6% stated that they received training on occupational safety; 27.1% reported having been absent from work for health reasons; 27.1% reported health complaints; 10% reported having a diagnosis of morbidity; 60% sought health services. Regarding work conditions, 78.9% considered their work conditions to be satisfactory; 65.2% stated that the work organization is critical; 76.3% claimed that socio-professional relationships are satisfactory; 63.9% considered the physical cost to be critical; 54.8% critical cognitive cost; and 67.6% satisfactory affective cost. In general, the variables that had a positive effect on quality of life and its domains were: the practice of physical activity; the cognitive and affective cost; the time spent working in soybean farms; the fact of being “live-in” employees; being unionized; workload during the harvest; and sun exposure. The variables that had negative effects on quality of life and its domains were: complaints and diagnosis of morbidity; cardiovascular risk; exposure to noise and dust; use of the private health service; alcohol addiction; medication use; socio-professional relationships; use of public transport; number of children; accident at work; and absence from work for health reasons. Conclusion: the factors that most impacted the quality of life of rural workers were related to the health conditions of these workers (using medication, having complaints and diagnoses of morbidity, use of health services, exposure to stressors [noise and dust], sedentary lifestyle, alcohol addiction). Work conditions, with a special focus on socio-professional relationships resulting from work activity, produced a negative impact on the quality of life of the investigated workers.